C-X-C motif chemokine ligand 12—C-X-C chemokine receptor type 4 signaling axis in cancer and the development of chemotherapeutic molecules - Jui-Hung Yen; Chun-Chun Chang; Hao-Jen Hsu; Chin-Hao Yang; Hemalatha Mani; Je-Wen Liou (Tzu Chi Medical Journal)
Chemokines are small, secreted cytokines crucial in the regulation of a variety of cell functions. The binding of chemokine C-X-C motif chemokine ligand 12 (CXCL12) (stromal cell-derived factor 1) to a G-protein-coupled receptor C-X-C chemokine receptor type 4 (CXCR4) triggers downstream signaling pathways with effects on cell survival, proliferation, chemotaxis, migration, and gene expression. Intensive and extensive investigations have provided evidence suggesting that the CXCL12-CXCR4 axis plays a pivotal role in tumor development, survival, angiogenesis, metastasis, as well as in creating tumor microenvironment, thus implying that this axis is a potential target for the development of cancer therapies. The structures of CXCL12 and CXCR4 have been resolved with experimental methods such as X-ray crystallography, NMR, or cryo-EM. Therefore, it is possible to apply structure-based computational approaches to discover, design, and modify therapeutic molecules for cancer treatments. Here, we summarize the current understanding of the roles played by the CXCL12-CXCR4 signaling axis in cellular functions linking to cancer progression and metastasis. This review also provides an introduction to protein structures of CXCL12 and CXCR4 and the application of computer simulation and analysis in understanding CXCR4 activation and antagonist binding. Furthermore, examples of strategies and current progress in CXCL12-CXCR4 axis-targeted development of therapeutic anticancer inhibitors are discussed.